Mitochondrial genome of Diaphorencyrtus aligarhensis (Hymenoptera: Chalcidoidea: Encyrtidae) and phylogenetic analysis. Issue 2 (3rd July 2019) - Du, Yimin; Song, Xiang; Liu, Xinjun; Zhong, Balian
Abstract: Diaphorencyrtus aligarhensis is an important natural enemy of the psyllid Diaphorina citri Kuwayama, a vector of the huanglongbing (HLB). Here, we sequenced and annotated the mitochondrial genome (mitogenome) of D. aligarhensis . This mitogenome was 16, 264 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and two ribosomal RNA unit genes (rRNAs). All 13 PCGs were initiated by the ATN (ATG, ATT, ATA, and ATC) codon. All PCGs terminate with the stop codon TAA except for cox2 and nad1 which end with the incomplete codon T−. Phylogenetic analysis showed that D. aligarhensis got together with the same family species Encyrtus infelix, and Encyrtidae had a close relationship with Agaonidae.